THE INFLUENCE OF THE PRINCIPAL'S MANAGERIAL ABILITY, TRAINING AND SPIRITUAL INTELLIGENCE ON TEACHER PERFORMANCE AT SMPN 1 RANTEPAO - Timang, Meti; Nadeak, Bernadetha; Sihotang, Hotmaulina (International Journal of Research -GRANTHAALAYAH, 2021)
The purpose of this study was to find out the influence of the headmaster's managerial ability on teacher performance, the influence of Teacher Spiritual Intelligence on Teacher performance, the influence of Teacher Training on student achievement, the influence of the principal's managerial ability, teacher training and spiritual intelligence on teacher performance at SMP Negeri 1 Rantepao. The method used in this research is a research method that is more towards the objective measurement aspect of social phenomena. The results showed that referring to the results of double linear regression analysis, and it can be concluded that managerial ability, training and spiritual intelligence have a significant and positive effect on teacher performance at SMP Negeri 1 Rantepao, meaning that if managerial ability, training and spiritual intelligence improve then the performance of teachers at SMP Negeri 1 Rantepao increased.